Synthesis, Characterization, and Photocatalytic Activity of CeBiO3 and FeBiO3 Nanoparticles Prepared via the Sol-Gel Process - Badaoui, M.; Sehil, H.; Lamouri, C. (Karagandy University of the name of academician E.A. Buketov, 2025)
This study investigated the photocatalytic potential of perovskite materials, cerium(III) bismuthate (CeBiO3) and iron(III) bismuthate (FeBiO3), for organic dye degradation under visible LED light illumination. The materials were synthesized via the sol-gel method and characterized using X-ray diffraction (XRD), Fouriertransform infrared spectroscopy (FT-IR), diffuse reflectance spectroscopy (DRS), and point of zero charge (PZC) analysis. A rhombohedral structure for FeBiO3 and a tetragonal structure for CeBiO3 with band gaps of 2.18 eV and 2.17 eV, respectively were revealed by structural characterization. The kinetic evolution of Methylene Blue (MB) degradation in an aqueous medium was examined. Both catalysts showed remarkable degradation efficiency, and CeBiO3 demonstrated superior performance. Optimal degradation conditions were achieved at pH 10, with a catalyst concentration of 0.15 g/L, an initial Methylene Blue concentration of 10 mg/L, and a reaction time of 4 hours. Overall, this study highlights the potential of perovskite materials CeBiO3 and FeBiO3 to efficiently degrade organic dyes under visible light and contributes to the development of sustainable wastewater treatment solutions.
Keywords: perovskite; nanoparticles; sol-gel; cerium(III) bismuthate; iron(III) bismuthate; photocatalysis; dye degradation; band gap